Integrated proteomics reveals alterations in sarcomere composition and developmental processes during postnatal swine heart development. (March 2023) - Aballo, Timothy J.; Roberts, David S.; Bayne, Elizabeth F.; Zhu, Wuqiang; Walcott, Gregory; Mahmoud, Ahmed I.; Zhang, Jianyi; Ge, Ying
Abstract: The neonatal swine heart possesses an endogenous ability to regenerate injured myocardium through the proliferation of pre-existing cardiomyocyte (CM) populations. However, this regenerative capacity is lost shortly after birth. Normal postnatal developmental processes and the regenerative capacity of mammalian hearts are tightly linked, but not much is known about how the swine cardiac proteome changes throughout postnatal development. Herein, we integrated robust and quantitative targeted "top-down" and global "bottom-up" proteomic workflows to comprehensively define the dynamic landscape of the swine cardiac proteome throughout postnatal maturation. Using targeted top-down proteomics, we were able to identify significant alterations in sarcomere composition, providing new insight into the proteoform landscape of sarcomeres that can disassemble, a process necessary for productive CM proliferation. Furthermore, we quantified global changes in protein abundance using bottom-up proteomics, identified over 700 differentially expressed proteins throughout postnatal development, and mapped these proteins to changes in developmental and metabolic processes. We envision these results will help guide future investigations to comprehensively understand endogenous cardiac regeneration toward the development of novel therapeutic strategies for heart failure. Graphical abstract: Unlabelled Image